2017
DOI: 10.1007/s00417-017-3852-1
|View full text |Cite
|
Sign up to set email alerts
|

Real-life clinical data for dexamethasone and ranibizumab in the treatment of branch or central retinal vein occlusion over a period of six months

Abstract: In a clinical setting, comparable improvement in BCVA and CRT were observed after DEX and IVR injections for treatment of BRVO. CRVO patients showed greater benefit with IVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Unlike them, we found that dex imp group has lower CMT and higher BCVA at month six. In a recent study, Sibylle et al compared dexamethasone and ranibizumab in BRVO and CRVO patients (24). Similar to our study, they performed additional dex imp based on clinical data.…”
Section: Discussionsupporting
confidence: 72%
“…Unlike them, we found that dex imp group has lower CMT and higher BCVA at month six. In a recent study, Sibylle et al compared dexamethasone and ranibizumab in BRVO and CRVO patients (24). Similar to our study, they performed additional dex imp based on clinical data.…”
Section: Discussionsupporting
confidence: 72%
“… Non-naive 32 66.5 (12.9) 56.2 Retrospective, multi-centre 48.7 ± 30.2 weeks Ozkaya et al [ 50 ] Turkey Dexamethasone 0.7 mg Single implant then PRN regimen. Naive 41 63.1 (11.1) 46.3 Retrospective, single-centre 24 Winterhalter et al [ 43 ] Germany Dexamethasone 0.7 mg Single implant then PRN regimen. Non-naive 31 c c Retrospective, single-centre 6 Yoon et al [ 44 ] South Korea Dexamethasone 0.7 mg Single implant then 4 monthly PRN regimen.…”
Section: Resultsmentioning
confidence: 99%
“… Unclear 54 65 50 Retrospective, single-centre 12 Osaka et al [ 110 ] Japan Ranibizumab 0.5 mg Single injection then monthly PRN regimen Naive 32 68.1 (11.1) 53.13 Prospective, single-centre 12 Ozkaya et al [ 50 ] Turkey Ranibizumab 0.5 mg Three monthly injections then monthly PRN regimen. Naive 46 60.8 (8.7) 30.4 Retrospective, single-centre 24 Winterhalter et al [ 43 ] Germany Ranibizumab 0.5 mg Three monthly injections, then further sets of 3 monthly injections PRN if active disease. Naive 27 c c Retrospective, single-centre 6 Son et al a [ 94 ] South Korea Ranibizumab 0.5 mg Three monthly injections then PRN regimen.…”
Section: Resultsmentioning
confidence: 99%
“…12 We found only one study that compared anti-VEGF and other treatments using real world data, that of Winterhalter et al who present data on visual acuity after 6 months of treatment with ranibizumab (n=58) or dexamethasone (n=48) and found improvements in the mean visual acuity of both groups (from 59.5 to 67 and from 54.5 to 65.5). 13 The UK EMR Users group has previously analysed data obtained from an electronic medical record (EMR), first looking at patients with age-related macular degeneration and then patients with diabetic macular oedema. They found that real world visual outcomes were not as good as those in clinical trials but that the studied treatments were nevertheless effective, and effective in wider populations than were included within the criteria of relevant trials.…”
Section: Introductionmentioning
confidence: 99%